Aplikasi PGPR, Trichoderma sp. dan Bokashi Kiambang (Pistia stratiotes L.) Untuk Mengendalikan Penyakit Layu Fusarium Pada Padi Beras Merah (Oryza nivara L.) Di Lahan Basah - Krisnawati, Wiwik; Budi, Ismed Setya; Marsuni, Yusriadi (JURNAL PROTEKSI TANAMAN TROPIKA, 2025)
Red rice is starting to be widely cultivated because of its health benefits, but its cultivation often experiences problems, one of which is fusarium wilt disease. The aim of this research is to determine the effect of PGPR (Plant Growth Promoting Rhizobacteria), Trichoderma sp. and Bokashi Kiambang on the incidence of fusarium wilt disease in red rice. Method using completely randomized design. The research was conducted in the wetlands of Cempaka sub-district, Banjarbaru. This observation was carried out four times, namely before treatment, ten days after the first treatment and every 10 days. The results of observations of the incidence of fusarium wilt disease were yellowish green leaves appeared, quickly dried and the plants died. The results of disease incidence in the PGPR application treatment, Trichoderma sp and bokashi kiambang had no effect. PGPR, Trichoderma sp and bokashi kiambang had no effect because the rice plants entered the generative phase. Use of a combination of PGPR, Trichoderma sp. and bokashi kiambang can increase the number of grains/panicles in 60 days of treatment. 70 days and 80 days was 223.00 grains/panicle, while in the control it was only 147.00 grains/panicle. The results of using a combination of PGPR, Trichoderma sp. and bokashi kiambang can increase the weight of 100 grains weighing 2.18 g compared to the control of only 1.15 g.